Nanoscale Design of Pd‐Based Electrocatalysts for Oxygen Reduction Reaction Enhancement in Alkaline Media. Issue 2 (7th January 2022) - Zhou, Ming; Guo, Jiangna; Fang, Jiye
Abstract : Palladium (Pd)‐based electrocatalysts have recently emerged as one class of the foremost promising candidates for the oxygen reduction reaction (ORR) in alkaline media due to their excellent ORR activity and durability and lower costs compared with platinum. Insightful design of Pd‐based nano‐architectures with optimized active surface sites and maximal intrinsic performance is central to promoting the ORR applications. To further accelerate the sluggish ORR kinetics at the cathode of fuel cells and substantially decrease the overall cost of the electrocatalysts, various strategies, including controlled sizes and shapes with selected crystallographic facets, crystal‐phase engineering, heteroatom doping, tailored surface strains, and surface engineering by de‐alloying, have been extensively developed in the past decade. In this review, a brief introduction to the fundamental ORR mechanisms of Pd‐based electrocatalysts in alkaline media is presented, followed by a thorough discussion on various strategies for delicately designing high‐performance Pd‐based catalysts with corresponding examples. Thereafter, the perspectives and new insights into the challenges are outlined, and some emerging research directions related to the rational design and controlled synthesis of Pd‐based ORR electrocatalysts are also proposed. Abstract : This review focuses on palladium (Pd)‐based electrocatalysts for the oxygen reduction reaction (ORR) in alkaline media. After a brief introduction and fundamental ORR mechanism overview, various strategies for delicately designing high‐performance Pd‐based catalysts are throughout discussed, together with associated examples. Perspectives with challenges and new insights are further outlined, and some emerging research directions are also proposed.